Аgro-industrial clusters in the west Africa countries - Y. E. Gouly (Путеводитель предпринимателя)
In the article experience of development of agro-industrial clusters in the west Africa countries. In the modern world, the development of agro-industrial clusters provides favorable conditions for creating an environment of production and introduction of high technologies, and also enables socio-economic growth of the region.